THE CHALLENGES OF APPLICATION OF THE HYBRID LEARNING MODEL IN GEOGRAPHY LEARNING DURING THE COVID-19 PANDEMIC - Singgih Prihadi; Sajidan Sajidan; Siswandari Siswandari; Sugiyanto Sugiyanto (Universitas Sebelas Maret (UNS), 2022)
Since the beginning of 2020, the COVID-19 pandemic has occurred, Indonesia has implemented distance learning. Higher education also conducts learning with a hybrid learning model. The hybrid learning model applied is of the full type, meaning that it is carried out fully online. Geography learning that is carried out online is still trying to equip students to increase spatial citizenship skills. This study seeks to find out how the challenges of implementing the hybrid learning model in geography learning in the geography education study program are FKIP UNS. The method used in this research is descriptive qualitative. The research subjects were second semester students, geography education study program FKIP UNS. The data collection techniques used were interviews, observations and FGD. The result of this research is that geography learning, which is carried out using a hybrid learning model, can effectively achieve mastery of students spatial citizenship skills. The hybrid learning model that is applied must be combined with other platforms such as Zoom Meeting, Moodle, WhatsApp and Open Course Ware.